Manajemen Keuangan Sekolah Berbasis Artificial Intelligence (AI) untuk Pemenuhan Standar Digitalisasi Sekolah Dasar - Ahmad Gawdy Prananosa; M. Rusni Eka Putra; Marianita Marianita; Lendri Alpikar (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze Artificial Intelligence (AI)-based school financial management to meet the digitalization standards for elementary schools. The research method used was a mixed qualitative-quantitative approach with an Educational Action Research design, involving 60 respondents from school principals, teachers, and education personnel. Data collection techniques included observation, Likert-scale questionnaires, and documentation. Data analysis was conducted descriptively and thematically through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of AI-based school financial management received a positive response from respondents across all aspects of financial management, including financial planning, financial management, reporting and transparency, auditing and evaluation, and system ethics and security. AI was perceived to improve the effectiveness, efficiency, accountability, and transparency of school financial management in an integrated and data-driven manner. The conclusion of this study indicates that Artificial Intelligence (AI)-based school financial management plays a strategic role in supporting the fulfillment of elementary school digitalization standards. However, its successful implementation depends heavily on infrastructure readiness, clear regulations, strengthened ethics, data security, and support from school management to ensure responsible and sustainable AI utilization.   Keywords: School Financial Management, Artificial Intelligence, School Digitalization, Elementary Schools, AI Ethics